Mapping the trading behavior of the middle class in emerging markets: Evidence from the Istanbul Stock Exchange - Bamiatzi, Vassiliki Vicky; Bozos, Konstantinos; Lambertides, Neophytos (My University, 2016)
Predicted to grow above 4.9 billion by 2030, with an overall spending capacity of $56 trillion, the rise of the middle class in emerging markets has attracted global practitioner and academic attention. How this new wealth will be invested is a central question; yet our understanding still remains fragmented. Drawing on the literatures of international business, behavioral economics and finance and using high-frequency stock market data, we examine and map the trading behavior of the middle class in Turkey, one of the fastest rising economic powers of the East. We find that middle class traders exhibit discernible differences to professionals, with respect to risk attitudes and stock preferences (e.g. prefer lower-risk, smaller-size and 'value' stocks). In addition, while they typically hold small portfolios and tend to realize lower gains than professionals, their role has become considerably influential to the direction of the entire market.
Keywords: Emerging markets; High frequency data; Istanbul Stock Exchange; Middle class; Trading behavior